Alkali metal complexes of bis-o-xylyl-(17-crown-5): from a dinuclear monomer and a dinuclear polymer to sandwich polymer. Issue 34 (6th August 2020) - Kim, Seulgi; Park, In-Hyeok; Lee, Shim Sung; Sim, Wonbo; Lee, Jai Young
Abstract : The self-assembly reactions of bis- o -xylyl-(17-crown-5) with alkali metal salts afforded binding mode (good fit, perching and sandwich)-dependent supramolecular complexes, including a sandwich-type cesium(i ) coordination polymer. Abstract : Herein, alkali metal complexes of bis- o -xylyl-(17-crown-5) (L ) with different binding modes are reported. When NaI was reacted with L, a disodium(i ) complex of the type [Na2 (L )(H2 O)2 ]I2 (1 ) with a good fit mode was isolated, providing the crown unit as a base of the pentagonal pyramid and a water molecule at its apex. However, the use of KPF6 gave a one dimensional (1-D) coordination polymer of type [K2 (L )(PF6 )2 ] n (2 ), in which dipotassium(i ) complex units with a perching mode are linked by two PF6 − ions to form an infinite zigzag chain. A cesium(i ) ion is large enough to bind two crown units from different ligands with a sandwich mode to give a 1-D sandwich polymer of the type {[Cs(L )]Cl} n (3 ) as a first example, which might be applied as a networking tool in crystal engineering.